2011
DOI: 10.1538/expanim.60.363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Levonorgestrel on Reproductive Hormone Levels and Their Receptor Expression in Mongolian Gerbils (Meriones unguiculatus)

Abstract: Abstract:The effects of levonorgestrel (LNG) on serum levels of reproductive hormones and their receptor mRNA expression in the ovary and uterus of Mongolian gerbils were examined. The results show that serum follicle-stimulating hormone (FSH) and luteinizing hormone (LH) increased, whereas serum estradiol (E2) and progesterone (P4) decreased profoundly after LNG treatment. LNG down-regulated the mRNA expression of folliclestimulating hormone receptor (FSHR), luteinizing hormone receptor (LHR), estrogen recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Acting on the hypothalamicpituitary-gonadal axis, it exerts a strong anti-gonadotropic effect in the hypothalamus, inhibiting ovulation, thickening the uterus, reducing uterine mucus, and inhibiting progesterone secretion. Our findings are consistent with the results of a study on gerbils with a single LNG exposure and SD rats receiving olive oil (0.2 ml/100 g/ day) containing a combination of 1.0 mg ethinylestradiol and 10.0 mg levonorgestrel (30,31). A small randomized controlled trial reported significantly reduced TSH levels in a 12-week trial of oral trace progesterone, 300 mg/d at bedtime, in postmenopausal women (32), which is consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Acting on the hypothalamicpituitary-gonadal axis, it exerts a strong anti-gonadotropic effect in the hypothalamus, inhibiting ovulation, thickening the uterus, reducing uterine mucus, and inhibiting progesterone secretion. Our findings are consistent with the results of a study on gerbils with a single LNG exposure and SD rats receiving olive oil (0.2 ml/100 g/ day) containing a combination of 1.0 mg ethinylestradiol and 10.0 mg levonorgestrel (30,31). A small randomized controlled trial reported significantly reduced TSH levels in a 12-week trial of oral trace progesterone, 300 mg/d at bedtime, in postmenopausal women (32), which is consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
“…The low serum progesterone levels in this study indicated that exogenous progestin could directly inhibit progesterone secretion by inhibiting the ovary. Progesterone directly suppresses estrogen and progesterone production by ovarian granulosa cells ( 30 , 31 ). Acting on the hypothalamic-pituitary-gonadal axis, it exerts a strong anti-gonadotropic effect in the hypothalamus, inhibiting ovulation, thickening the uterus, reducing uterine mucus, and inhibiting progesterone secretion.…”
Section: Discussionmentioning
confidence: 99%